1965
DOI: 10.1017/s0033822200037176
|View full text |Cite
|
Sign up to set email alerts
|

University of Pennsylvania Dates VII

Abstract: Measurements of samples of known age have been undertaken in this laboratory since its beginning in 1951 when it was found that modern wood samples taken from the outer rings of young trees did not afford a basis of counter calibration consistent with archaeologically dated samples (Ralph, 1955). This depletion was explained by Suess (1955). Subsequent measurements of samples representative of the early Egyptian dynasties, however, revealed that even with the counter calibration corrected for the modern deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1968
1968
1974
1974

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…First of all, three laboratories (Tucson, Philadelphia and La Jolla)" presented in one form or another their measurements of tree-ring dated samples, mainly from bristle-cone pine wood supplied by C. W. Ferguson. These results have already been partly published (Suess, 1965, Ralph et al, 1965Damon et al, 1966;Suess, 1967;Ralph et al, 1968) or will be published in the near future. All the measurements from the three laboratories show the same overall picture of deviations known previously: slight variations in the last 2,000 years and then a steady growth of deviations back to 5150 BC when the present tree-ring calendar begins.…”
Section: Logy D E V I a T I O N S Of R A D I O C A R B O N Ages F R mentioning
confidence: 70%
“…First of all, three laboratories (Tucson, Philadelphia and La Jolla)" presented in one form or another their measurements of tree-ring dated samples, mainly from bristle-cone pine wood supplied by C. W. Ferguson. These results have already been partly published (Suess, 1965, Ralph et al, 1965Damon et al, 1966;Suess, 1967;Ralph et al, 1968) or will be published in the near future. All the measurements from the three laboratories show the same overall picture of deviations known previously: slight variations in the last 2,000 years and then a steady growth of deviations back to 5150 BC when the present tree-ring calendar begins.…”
Section: Logy D E V I a T I O N S Of R A D I O C A R B O N Ages F R mentioning
confidence: 70%
“…Those designated "P-SW-" only, were coil, dendro-dated, and subm by H N Michael, Mus Applied Sci Center for Archaeol, Univ Mus and were processed by the Univ Pennsylvania lab. All samples designated P-SW-INY-in Tables 1 and 2 are Pinus aristata; others are Sequoia gigan tea. H N Michael and E K Ralph 199 The provenience of most of the samples was published in Ralph et al (1965), and Ralph and Michael (1969 Calibration curves shown in figs 1-6 are based on >600 precisely dated samples processed by the 3 labs mentioned earlier. These curves were based on a 9-cell regression weighted averaging of the raw data, centered on each mid-point.…”
mentioning
confidence: 99%
“…Those designated "P-SW-" only, were coil, dendro-dated, and subm by H N Michael, Mus Applied Sci Center for Archaeol, Univ Mus and were processed by the Univ Pennsylvania lab. All samples designated P-SW-INY-in Tables 1 and 2 are Pinus aristata; others are Sequoia gigan tea. The provenience of most of the samples was published in Ralph et al (1965), and Ralph and Michael (1969). Two new series appear below.…”
mentioning
confidence: 99%